PC hardware in a nutshell : a desktop quick reference - Thompson, Robert Bruce; Thompson, Barbara Fritchman (New Delhi : SPD, 2003)
PC Hardware in a Nutshell is the practical guide to buying, building, upgrading, and repairing Intel-based PCs. A longtime favorite among PC users, the third edition of the book now contains useful information for people running either Windows or Linux operating systems. Written for novices and seasoned professionals alike, the book is packed with useful and unbiased information, including how-to advice for specific components, ample reference material, and a comprehensive case study on building a PC.In addition to coverage of the fundamentals and general tips about working on PCs, the book includes chapters focusing on motherboards, processors, memory, floppies, hard drives, optical drives, tape devices, video devices, input devices, audio components, communications, power supplies, and maintenance. Special emphasis is given to upgrading and troubleshooting existing equipment so you can get the most from your existing investments.
Includes index.
Keywords: Microcomputers -- Equipment and supplies; Microcomputers -- Upgrading; Microcomputers -- Maintenance and repair